The social significance of homogamy - Malcolm Brynin; Simonetta Longhi; Álvaro Martínez Pérez (University of Essex, Institute for Social and Economic Research (ISER), 2008)
It is a long-standing principle in anthropology, sociology but also economics, that there are strong social and material incentives for people to marry or partner on the basis of social similarity, thus encouraging equality within partnerships but social inequality in the distribution of education, income, or other characteristics. It has been argued, however, that marriage is becoming less homogamous, and therefore that society is becoming more open. Using both the Longitudinal Study and the British Household Panel Study, we find that homogamy remains a powerful factor in marriage and partnership. Further, it reduces stress levels in the partnership and increases over the period of the relationship as partners social and political attitudes become closer over time.
Keywords: 330